Word Formation of the Indonesian Covid-19 Special Terms - Taat Budiono; Yasir Mubarok (Buletin Al-Turas, 2022)
PurposeThis study was intended to describe the process of forming the Covid-19 outbreak-related special terms in Indonesian sourcing from English. MethodThe research employed a qualitative approach which a descriptive case study design. Its primary data consisted of words and phrases associated with Covid-19 taken from news articles on the Kompas.com page during March-July 2020 using a note-taking technique. The data were then analyzed qualitatively by considering the concepts of word formation in Indonesian. Results/FindingsTh research revealed that the forming of the Covid-19 related special terms were through absorption (49%), translation (32%), and through the creation of new concepts (19%). This indicates that the absorption of English terms into Indonesian was the most dominant process. English a global language was widely absorbed by other languages, including Indonesian. ConclusionThe research shows that Covid-19 outbreak-related special terms was classified into English terms and Indonesian terms. The terms experienced three formation processes, namely the absorption, translation, and the creation of new concepts